The Search for the Perfection of Divine Love in Herman Hesse's Novel Sidharta - Purnamasari, Hetty; Amrullah, Imron (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article discusses Siddharta's journey in finding a teacher through long twists and turns, joys and sorrows, praise and trials one after another does not discourage him because of his great love and love for the Divine. Siddharta who is intelligent and has a perfect physical form and attitude, gets affection from his parents and is about to be dissatisfied and satisfied. His heart still has an empty space for Divine love. The figures and the environment in Siddharta as teachers, whatever comes from them, they can always learn. The protagonists move with flexible, balanced sentences, not only in everyday discourse and textual discourse. The figures with beautiful movements, so a lot of spiritual development. The characters who get control of the environment they are in. No coincidence is coincidence, making this novel appear as a profound reflection.